Environmental and social issues of land use planning (LUP) in property development: A case study at Tg. Tokong, Penang - Khalil, Samihah; Mariyappan, Raman; Ismail, Mazlan (Universiti Utara Malaysia, 2011)
A systematic land use planning plays an important role towards a better environmental resources development.Land being the vital ingredient in any development needs a better understanding and systematic planning. This closely rooted towards sustainable land use development. Ignorance towards a systematic land use planning can cause various problems related to the physical environment and to the humans.This can be seen clearly in Penang Island, where land is considered a vital component in developing the Island’s ever growing property sector. As the state push towards fulfilling the demand in the property sector, environmental problems such as slope failure, mud-flood, severe coastal erosion, vanishing green lungs, frequent flash floods, river pollutions, and disruption of coastal process becomes liability to the environmental sustainability of the Island.The three day Star Property Fair 2010 in Penang concluded with RM50m worth of property sold in the Penang Island. This is an indication that demand for residential and commercial property in Penang Island is so great exceeding the states’ and the developers’ projections.The social issues such as displacement of traditional villages, disappearing fishing communities, increasing number of vulnerable group and many other related issues due to development. This study will be focusing on the environmental and social issues related to past, present and future land use planning at Tg. Tokong, Penang.